Cobalt-selenium co-doped carbon nanotube and preparation method and application thereof
By using co-doped carbon nanotube materials in lithium-sulfur batteries, the problems of poor cycle stability and fast capacity decay of lithium-sulfur batteries are solved, and the effects of improving electrode conductivity and extending cycle life are achieved.
Patent Information
- Application Number
- CN202510021860.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The poor circulation stability and fast capacity decay of lithium-sulfur batteries are mainly due to the poor conductivity of sulfur electrodes and the dissolution of polysulfides.
Cobalt-selenium co-doped carbon nanotubes (Co-CoSe@CNT) are used as the main material of sulfur. Through synergistic action, the chemical adsorption capacity of the electrode material is enhanced, polysulfide is captured and physical barriers are provided, and the cycle life of lithium-sulfur batteries is extended.
It significantly improves the electrode conductivity, enhances the cycle stability, optimizes the electrochemical performance, and extends the cycle life of lithium-sulfur batteries.
Smart Images

Figure CN119706812A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon nanotube materials, and in particular relates to a cobalt-selenium co-doped carbon nanotube and a preparation method and application thereof. Background Art
[0002] At present, with the rapid development of renewable energy technology, the importance of high-performance energy storage systems has become increasingly prominent. Lithium-sulfur batteries have become the focus of the industry due to their high energy density, low cost and environmental friendliness. Compared with traditional lithium-ion batteries, lithium-sulfur batteries show higher theoretical energy density, which means that they can store more considerable energy at the same volume or weight. In addition, lithium-sulfur batteries have significant cost advantages, mainly due to their abundant sulfur and lithium resources and relatively simple production processes. More importantly, lithium-sulfur batteries produce less environmental pollution during production and use, which perfectly meets the needs of the era of sustainable development.
[0003] However, despite the huge potential of lithium-sulfur batteries, their widespread application is still restricted by problems such as poor cycle stability and rapid capacity decay. This is mainly due to the poor conductivity of the sulfur electrode in lithium-sulfur batteries and the dissolution of polysulfides, which directly lead to rapid capacity decay and decreased cycle stability. Summary of the invention
[0004] The purpose of the embodiments of the present invention is to provide a method for preparing cobalt-selenium co-doped carbon nanotubes, aiming to solve the problems raised in the above background technology.
[0005] The embodiment of the present invention is implemented as follows: a method for preparing cobalt-selenium co-doped carbon nanotubes comprises the following steps: Synthesis of ZIF-67@CNT precursor: adding cobalt nitrate hexahydrate and carbon nanotubes to a methanol solution, stirring and dissolving them to obtain a solution A; dissolving 2-methylimidazole in the methanol solution, stirring and evenly obtaining a solution B; mixing the solution A and the solution B, stirring continuously to form a purple precipitate, separating and washing the precipitate, and vacuum drying the washed precipitate to obtain a ZIF-67@CNT precursor; Synthesis of Co-CoSe@CNT: ZIF-67@CNT precursor and selenium powder were placed in a tubular furnace. Under an argon gas flow, the furnace temperature was increased and kept warm, and then cooled to room temperature to obtain Co-CoSe@CNT.
[0006] Preferably, in the step of synthesizing the ZIF-67@CNT precursor, the carbon nanotubes are multi-walled long nanotubes with a length of less than 10 μm and a diameter of 30-50 nm.
[0007] Preferably, in the step of synthesizing the ZIF-67@CNT precursor, solution A and solution B are mixed and stirred for 8-12 hours.
[0008] Preferably, in the step of synthesizing the ZIF-67@CNT precursor, the temperature of vacuum drying the washed precipitate is 60-80° C. and the time is 12-18 h.
[0009] Preferably, in the step of synthesizing Co-CoSe@CNT, the ZIF-67@CNT precursor and selenium powder are placed in a tubular furnace, the selenium powder is placed in the upstream area of the tubular furnace, and the ZIF-67@CNT precursor is evenly placed in the center of the tubular furnace.
[0010] Preferably, in the step of synthesizing Co-CoSe@CNT, the furnace temperature is increased and kept warm under an argon gas flow, the flow rate of the argon gas flow is 10-30 mL / s, the furnace temperature is increased to 800°C at a heating rate of 3-5°C / min, and kept warm for 3-4 hours.
[0011] Another object of an embodiment of the present invention is to provide a cobalt-selenium co-doped carbon nanotube, which is prepared by the above preparation method.
[0012] Another object of the embodiment of the present invention is to provide an application of cobalt-selenium co-doped carbon nanotubes in the preparation of lithium-sulfur batteries.
[0013] Preferably, the steps include: Completely dissolving polyvinylidene fluoride in an N-methylpyrrolidone solution and performing magnetic stirring, adding the Co-CoSe@CNT under continuous magnetic stirring, continuing stirring, and then adding sulfur to form a uniform slurry under continuous magnetic stirring, and then uniformly coating the slurry on aluminum foil to obtain a sulfur-loaded Co-CoSe@CNT electrode material, and then vacuum drying the sulfur-loaded Co-CoSe@CNT electrode material and cutting it; A lithium-sulfur battery was prepared in a glove box environment under an argon atmosphere using sulfur-loaded Co-CoSe@CNT electrode material as the positive electrode material, metal lithium flakes as the negative electrode material, Celgard 2400 as the separator, and lithium bis(trifluoromethanesulfonyl)imide as the electrolyte.
[0014] The present invention provides a method for preparing cobalt-selenium co-doped carbon nanotubes, which uses diatomic cobalt (Co) and selenium (Se) co-doped carbon nanotube (CNT) materials as the main material of sulfur. The chemical adsorption capacity of the electrode material is significantly enhanced through synergistic effect, polysulfides are effectively captured, and excellent physical barrier properties are provided, thereby further suppressing the shuttle effect and extending the long cycle life of the lithium-sulfur battery, which is specifically reflected in the following three aspects: Improve electrode conductivity: Through the co-doping structure design of cobalt and selenium, the conductivity of carbon nanotube materials has been significantly improved; Enhanced cycle stability: The carbon nanotube structure not only strengthens the mechanical strength of the material, but also greatly enhances its adsorption efficiency for polysulfides, thereby significantly improving the cycle stability of lithium-sulfur batteries; Optimizing electrochemical performance: Through fine-tuning of synthesis conditions and optimizing material ratios, a more efficient charge transfer channel was constructed and a faster reaction kinetics process was achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1-2 This is a transmission electron microscopy image of the Co-CoSe@CNT sample prepared in Example 1 of the present invention; Figure 3 This is a transmission electron microscopy image of the precursor ZIF-67@CNT sample prepared in Example 1 of the present invention; Figure 4-5 This is a scanning electron microscope image of the Co-CoSe@CNT sample prepared in Example 1 of the present invention; Figure 6 This is a scanning electron microscope image of the precursor ZIF-67@CNT sample prepared in Example 1 of the present invention; FIG7 is an element mapping diagram of the Co-CoSe@CNT sample prepared in Example 1 of the present invention; FIG8 is a TG graph of the Co-CoSe@CNT sample prepared in Example 1 of the present invention; 9-12 are XPS images of Co-CoSe@CNT samples prepared in Example 1 of the present invention; FIG13 is an XPS graph of the precursor ZIF-67@CNT sample prepared in Example 1 of the present invention; FIG14 is an XRD pattern of the precursor ZIF-67@CNT sample prepared in Example 1 of the present invention; FIG15 is a Raman spectrum of the Co-CoSe@CNT sample prepared in Example 1 of the present invention; FIG16 is a Raman spectrum of the precursor ZIF-67@CNT sample prepared in Example 1 of the present invention; FIG17 is an EIS graph of the lithium-sulfur battery prepared in Example 1 of the present invention and other sample batteries; FIG18 is a cycle performance diagram of the lithium-sulfur battery prepared in Example 1 of the present invention at 0.2 C; FIG19 is a rate performance diagram of the lithium-sulfur battery prepared in Example 1 of the present invention; FIG20 is a graph showing the specific capacity-voltage of the lithium-sulfur battery prepared in Example 1 of the present invention at different rates. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0017] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.
[0018] Embodiment 1: A lithium-sulfur battery, the preparation method of which comprises the following steps: Step 1: Synthesis of ZIF-67@CNT precursor: (1) Prepare two containers, marked as container A and container B. In container A, weigh 1.465 g of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 1 g of carbon nanotubes (CNTs) (the carbon nanotubes are multi-walled long nanotubes with a length of less than 10 μm and a diameter of 30-50 nm), add them to 100 ml of methanol solution, and stir them for 8 h to ensure that the solid matter is completely dissolved; weigh 3.245 g of 2-methylimidazole in container B and dissolve it in an equal volume of methanol, and stir to form a uniform solution; (2) Mix the solutions in container A and container B, and continue stirring for 8 hours to allow 2-methylimidazole to fully react with cobalt nitrate to form a purple precipitate. After the reaction is completed, use a filter to separate the precipitate from the solution and wash it three times with methanol to completely remove the residual reactants and impurities; (3) The purple precipitate obtained by filtration was transferred into a crucible, and then placed in a vacuum drying oven and dried at 60 °C for 12 h. After drying, the desired ZIF-67@CNT precursor was obtained; Step 2: Synthesis of Co-CoSe@CNT: The dried precursor was heat treated in a tube furnace, 0.15 g of selenium powder and 1 g of ZIF-67@CNT precursor were placed in the tube furnace (selenium powder was placed in the upstream area of the tube furnace, and ZIF-67@CNT precursor was evenly placed in the center of the tube furnace), and the furnace temperature was gradually increased to 800°C at a rate of 5°C / min under an argon gas flow of 25 mL / s, and maintained at 800°C for 3 h. After cooling to room temperature, Co-CoSe@CNT was synthesized (after turning off the heating system, the tube furnace was allowed to cool naturally. During the cooling process, the newly formed Co-CoSe@CNT will gradually solidify, and a stable solid product will be obtained in the end); Step 3: Synthesis of sulfur-loaded Co-CoSe@CNT: 0.1 g of polyvinylidene fluoride (PVDF) was completely dissolved in N-methylpyrrolidone (NMP) solution and magnetically stirred for 0.5 h. Subsequently, 0.3 g of Co-CoSe@CNT was added to the mixture under continuous magnetic stirring and stirred for 1 h. Then, 0.6 g of ground sulfur (sulfur was sulfur powder dried in a blast drying oven for at least 2 h) was added to the mixture to form a uniform slurry under continuous magnetic stirring and stirred for 2 h. Finally, the slurry was uniformly coated on aluminum foil to obtain sulfur-loaded Co-CoSe@CNT, which was then completely dried at 80 ° C in a vacuum for 12 h and cut into discs with a diameter of 12 mm. Step 4: Preparation of lithium-sulfur battery: Sulfur-loaded Co-CoSe@CNT was used as the positive electrode material, combined with metallic lithium flakes as the negative electrode, Celgard2400 was selected as the separator, and 1 mol / L concentration of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was selected as the electrolyte. The electrolyte was dissolved by a mixed solvent of 1,3-dioxysilane and 1,2-dimethoxyethane in an equal volume ratio. Finally, the lithium-sulfur battery was assembled in a glove box environment under an argon atmosphere.
[0019] Embodiment 2: A lithium-sulfur battery, the preparation method of which comprises the following steps: Step 1: Synthesis of ZIF-67@CNT precursor: (1) Prepare two containers, labeled as container A and container B. In container A, weigh 2.93 g of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 2 g of carbon nanotubes (CNTs), then add them to 200 ml of methanol solution and stir for 8 h to ensure that the solid matter is completely dissolved. In container B, weigh 6.49 g of 2-methylimidazole and dissolve it in an equal volume of methanol. Stir to form a uniform solution. (2) Mix the solutions in container A and container B, and continue stirring for 12 hours to allow 2-methylimidazole to fully react with cobalt nitrate to form a purple precipitate. After the reaction is completed, use a filter to separate the precipitate from the solution and wash it three times with methanol to completely remove the residual reactants and impurities; (3) The purple precipitate obtained by filtration was transferred into a crucible, and then placed in a vacuum drying oven and dried at 80 °C for 12 h. After drying, the desired ZIF-67@CNT precursor was obtained; Step 2: Synthesis of Co-CoSe@CNT: The dried precursor was subjected to a tube furnace heat treatment. 0.3 g of selenium powder and 2 g of ZIF-67@CNT precursor were placed in a tube furnace. Under an argon gas flow rate of 15 mL / s, the furnace temperature was gradually increased to 800°C at 2°C / min. The temperature was maintained at 800°C for 4 h. After cooling to room temperature, Co-CoSe@CNT was synthesized. Step 3: Synthesis of sulfur-loaded Co-CoSe@CNT: 0.1 g of polyvinylidene fluoride (PVDF) was completely dissolved in N-methylpyrrolidone (NMP) solution and magnetically stirred for 0.5 h. Subsequently, 0.3 g of sulfur-loaded Co-CoSe@CNT was added to the mixture under continuous magnetic stirring and stirred for 1 h. Then, 0.6 g of ground sulfur was added to the mixture to form a uniform slurry under continuous magnetic stirring and stirred for 2 h. Finally, the slurry was uniformly coated on aluminum foil to obtain sulfur-loaded Co-CoSe@CNT, which was then completely dried at 80 ° C in a vacuum for 12 h and cut into discs with a diameter of 12 mm. Step 4: Preparation of lithium-sulfur battery: Sulfur-loaded Co-CoSe@CNT was used as the positive electrode material, combined with metal lithium flakes as the negative electrode, Celgard2400 was selected as the separator, and a 1 mol / L concentration of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) electrolyte was selected. The electrolyte was dissolved by dissolving a mixed solvent of 1,3-dioxysilane and 1,2-dimethoxyethane in an equal volume ratio. Finally, the lithium-sulfur battery was assembled in a glove box environment under an argon atmosphere.
[0020] Embodiment 3: A lithium-sulfur battery, the preparation method of which comprises the following steps: Step 1: Synthesis of ZIF-67@CNT precursor: (1) Prepare two containers, labeled as container A and container B. In container A, weigh 1.465 g of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 1 g of carbon nanotubes (CNTs), then add them to 100 ml of methanol solution and stir for 8 h to ensure that the solid matter is completely dissolved. In container B, weigh 3.245 g of 2-methylimidazole and dissolve it in an equal volume of methanol. Stir to form a uniform solution. (2) Mix the solutions in container A and container B, and continue stirring for 8 hours to allow 2-methylimidazole to fully react with cobalt nitrate to form a purple precipitate. After the reaction is completed, use a filter to separate the precipitate from the solution and wash it three times with methanol to completely remove the residual reactants and impurities; (3) The purple precipitate obtained by filtration was transferred into a crucible, and then placed in a vacuum drying oven and dried at 60 °C for 12 h. After drying, the desired ZIF-67@CNT precursor was obtained; Step 2: Synthesis of Co-CoSe@CNT samples: The dried precursor was subjected to a tube furnace heat treatment. 0.15 g of selenium powder and 1 g of ZIF-67@CNT precursor were placed in a tube furnace. The furnace temperature was gradually increased to 800°C at a rate of 5°C / min under an argon gas flow rate of 30 mL / s. The temperature was maintained at 800°C for 3 h. After cooling to room temperature, Co-CoSe@CNT was synthesized. Step 3: Synthesis of sulfur-loaded Co-CoSe@CNT: 0.05 g of polyvinylidene fluoride (PVDF) was completely dissolved in N-methylpyrrolidone (NMP) solution and magnetically stirred for 0.5 h. Subsequently, 0.15 g of sulfur-loaded Co-CoSe@CNT was added to the mixture under continuous magnetic stirring and stirred for 1 h. Then, 0.3 g of ground sulfur was added to the mixture to form a uniform slurry under continuous magnetic stirring and stirred for 2 h. Finally, the slurry was uniformly coated on aluminum foil to obtain sulfur-loaded Co-CoSe@CNT, which was then completely dried at 80 ° C in a vacuum for 12 h and cut into discs with a diameter of 12 mm. Step 4: Preparation of lithium-sulfur battery: Sulfur-loaded Co-CoSe@CNT was used as the positive electrode material, combined with metal lithium flakes as the negative electrode, Celgard2400 was selected as the separator, and a 1 mol / L concentration of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) electrolyte was selected. The electrolyte was dissolved by dissolving a mixed solvent of 1,3-dioxysilane and 1,2-dimethoxyethane in an equal volume ratio. Finally, the lithium-sulfur battery was assembled in a glove box environment under an argon atmosphere.
[0021] Performance Test: The precursor ZIF-67@CNT samples, Co-CoSe@CNT samples, lithium-sulfur batteries, etc. prepared in the process of Example 1 and prepared were characterized and electrochemical performance tested. The instruments used included: Morphology test: using field emission scanning electron microscope (FEI) and high-resolution transmission electron microscope (model G2 F20FEI Tecnai); Material structure and performance testing: using Renishaw thermo K-Alpha X-ray photoelectron spectrometer for in-depth analysis; Electrochemical performance test: The CHI6600E electrochemical workstation manufactured by Shanghai Chenhua Company was used to test the cyclic voltammetric characteristics and AC impedance of the battery; Charge and discharge test: Wuhan Blue Electric battery test system was used, which has a current range of 20 mA and a voltage range of 5 V.
[0022] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing cobalt-selenium co-doped carbon nanotubes, characterized in that: The following steps are involved: Synthesis of ZIF-67@CNT precursor: adding cobalt nitrate hexahydrate and carbon nanotubes into a methanol solution, stirring and dissolving them to obtain a solution A; Dissolve 2-methylimidazole in a methanol solution and stir evenly to obtain a solution B; mix the solution A and the solution B, continue stirring to form a purple precipitate, separate the precipitate and wash it, and vacuum dry the washed precipitate to obtain a ZIF-67@CNT precursor; Synthesis of Co-CoSe@CNT: ZIF-67@CNT precursor and selenium powder were placed in a tubular furnace. Under an argon gas flow, the furnace temperature was increased and kept warm, and then cooled to room temperature to obtain Co-CoSe@CNT.
2. The method for preparing cobalt-selenium co-doped carbon nanotubes according to claim 1, characterized in that: In the step of synthesizing the ZIF-67@CNT precursor, the carbon nanotubes are multi-walled long nanotubes with a length of less than 10 μm and a diameter of 30-50 nm.
3. The method for preparing cobalt-selenium co-doped carbon nanotubes according to claim 1, characterized in that: In the step of synthesizing the ZIF-67@CNT precursor, solution A and solution B are mixed and stirred for 8-12 hours.
4. The method for preparing cobalt-selenium co-doped carbon nanotubes according to claim 1, characterized in that: In the step of synthesizing the ZIF-67@CNT precursor, the washed precipitate is vacuum dried at a temperature of 60-80° C. for 12-18 hours.
5. The method for preparing cobalt-selenium co-doped carbon nanotubes according to claim 1, characterized in that: In the step of synthesizing Co-CoSe@CNT, ZIF-67@CNT precursor and selenium powder are placed in a tubular furnace, selenium powder is placed in the upstream area of the tubular furnace, and ZIF-67@CNT precursor is evenly placed in the center of the tubular furnace.
6. The method for preparing cobalt-selenium co-doped carbon nanotubes according to claim 1, characterized in that: In the step of synthesizing Co-CoSe@CNT, the furnace temperature is increased and kept warm under an argon gas flow, the flow rate of the argon gas flow is 10-30 mL / s, the furnace temperature is increased to 800° C. at a heating rate of 3-5° C. / min, and kept warm for 3-4 hours.
7. A cobalt-selenium co-doped carbon nanotube, characterized in that: The preparation method is as described in any one of claims 1 to 6.
8. Use of the cobalt-selenium co-doped carbon nanotubes as claimed in claim 7 in the preparation of lithium-sulfur batteries.
9. The use according to claim 8, characterized in that: The following steps are involved: Completely dissolving polyvinylidene fluoride in an N-methylpyrrolidone solution and performing magnetic stirring, adding the Co-CoSe@CNT under continuous magnetic stirring, continuing stirring, and then adding sulfur to form a uniform slurry under continuous magnetic stirring, and then uniformly coating the slurry on aluminum foil to obtain a sulfur-loaded Co-CoSe@CNT electrode material, and then vacuum drying the sulfur-loaded Co-CoSe@CNT electrode material and cutting it; A lithium-sulfur battery was prepared in a glove box environment under an argon atmosphere using sulfur-loaded Co-CoSe@CNT electrode material as the positive electrode material, metal lithium flakes as the negative electrode material, Celgard 2400 as the separator, and lithium bis(trifluoromethanesulfonyl)imide as the electrolyte.
Citation Information
Cited By
Negative electrode composite dispersing agent for sodium ion battery and preparation method of negative electrode composite dispersing agent
CN120767331A
A negative electrode composite dispersant for sodium-ion batteries and a preparation method thereof
CN120767331B